Role of extracorporeal membrane oxygenation in critically Ill COVID‐19 patients and predictors of mortality. Issue 6 (28th December 2020) - Zayat, Rashad; Kalverkamp, Sebastian; Grottke, Oliver; Durak, Koray; Dreher, Michael; Autschbach, Rüdiger; Marx, Gernot; Marx, Nikolaus; Spillner, Jan; Kersten, Alex
Abstract: The role of extracorporeal membrane oxygenation (ECMO) in the management of critically ill COVID‐19 patients remains unclear. Our study aims to analyze the outcomes and risk factors from patients treated with ECMO. This retrospective, single‐center study includes 17 COVID‐19 patients treated with ECMO. Univariate and multivariate parametric survival regression identified predictors of survival. Nine patients (53%) were successfully weaned from ECMO and discharged. The incidence of in‐hospital mortality was 47%. In a univariate analysis, only four out of 83 pre‐ECMO variables were significantly different; IL‐6, PCT, and NT‐proBNP were significantly higher in non‐survivors than in survivors. The Respiratory Extracorporeal Membrane Oxygenation Survival Prediction (RESP) score was significantly higher in survivors. After a multivariate parametric survival regression, IL‐6, NT‐proBNP and RESP scores remained significant independent predictors, with hazard ratios (HR) of 1.069 [95%‐CI: 0.986‐1.160], P  = .016 1.001 [95%‐CI: 1.000‐1.001], P  = .012; and .843 [95%‐CI: 0.564‐1.260], P  = .040, respectively. A prediction model comprising IL‐6, NT‐proBNP, and RESP score showed an area under the curve (AUC) of 0.87, with a sensitivity of 87.5% and 77.8% specificity compared to an AUC of 0.79 for the RESP score alone. The present study suggests that ECMO is a potentially lifesaving treatment for selected critically ill COVID‐19 patients. Considering IL‐6 and NT‐pro‐BNP, in addition to the RESP score, may enhance outcome predictions.